2015
DOI: 10.1016/j.jmb.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Yeast Hsp70, Ssa1, at P417 Alter ATP Cycling, Interdomain Coupling, and Specific Chaperone Functions

Abstract: The major cytoplasmic Hsp70 chaperones in the yeast Saccharomyces cerevisiae are the Ssa proteins, and much of our understanding of Hsp70 biology has emerged from studying ssa mutant strains. For example, Ssa1 catalyzes multiple cellular functions, including protein transport and degradation, and to this end the ssa1–45 mutant has proved invaluable. However, the biochemical defect(s) associated with the corresponding Ssa1–45 protein (P417L) are unknown. Consequently, we characterized Ssa1 P417L as well as a P4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 99 publications
2
16
0
Order By: Relevance
“…The magnitude of this effect mirrored the effect on the bacterial chaperones 26 , and the data are consistent with the ability of MAL1–271 to suppress the formation of α-synuclein aggregates in a neuroglioma cell model. 34 We also note that the turnover rate measured in these experiments (0.08 min-1) is consistent with published values for this chaperone 32 and that none of the pyrimidinone-peptoid hybrid molecules acts on Hsp90, consistent with their specific binding to the co-chaperone binding pocket in Hsp70. 26 …”
Section: Resultssupporting
confidence: 84%
“…The magnitude of this effect mirrored the effect on the bacterial chaperones 26 , and the data are consistent with the ability of MAL1–271 to suppress the formation of α-synuclein aggregates in a neuroglioma cell model. 34 We also note that the turnover rate measured in these experiments (0.08 min-1) is consistent with published values for this chaperone 32 and that none of the pyrimidinone-peptoid hybrid molecules acts on Hsp90, consistent with their specific binding to the co-chaperone binding pocket in Hsp70. 26 …”
Section: Resultssupporting
confidence: 84%
“…We speculated the efficient Htt103QP IB formation in each single mutant is likely due to the redundant function of Hsp70 protein family. To test this possibility, we used a strain lacking SSA2 , SSA3 and SSA4 genes but expressing temperature-sensitive ssa1-45 [ 35 ]. We found that this mutant showed a significant Htt103QP IB formation defect when incubated at 35°C.…”
Section: Resultsmentioning
confidence: 99%
“…To examine whether ROMK degradation is chaperone-dependent, we utilized a yeast strain containing a temperature-sensitive mutation in the gene encoding Ssa1. Specifically, in the ssa1-45 strain, a Pro to Leu mutation at residue 417 renders the resulting protein unstable at higher temperatures (81). When expressed in a strain that lacks the genes encoding the paralogous cytosolic Hsp70 proteins Ssa2, Ssa3, and Ssa4, defects in growth, protein translocation, and ERAD were evident at 37°C (82).…”
Section: The Degradation Of Bartter Mutants Is Facilitated By the Cdcmentioning
confidence: 99%